The Use of Low-Rejection Nanofiltration Membranes as a Tool to Simplify Pretreatment, Escape Scaling and Radically Increase Recoveries - Alexei G. Pervov; Dmitry Spitsov; Anna Kulagina; Htet Zaw Aung (Membranes)
This article describes the results of research to develop a new technology to treat storm and drainage water generated on a territory of industrial enterprises and reuse it as a feed water for boiler feed and steam generation. To develop such a system, it is necessary to resolve issues related to pretreatment, scaling, and fouling, as well as to provide a minimal discharge in the company’s sanitation network. Principles of the new approach to reach high calcium removal are based on the use of two or three stages of low-pressure nanofiltration membranes instead of the conventional facilities that contain one stage of reverse osmosis membranes. High permeability, low pressure, high recovery, and reduced reagent consumption provide an economic effect. The technology uses low-rejection membranes “nano NF” developed and produced by “Membranium Co.” (Vladimir, Russia). In the article, the results of investigations on the evaluation of scaling rates in membrane modules and rates of homogeneous crystallization in concentrate flow are presented. Processing these results enables us to detect recovery values when scaling begins on the membrane surface as well as to determine the maximum recovery value for the beginning of homogenous nucleation in the concentrate flow.